(untitled) (British Journal of Multidisciplinary and Advanced Studies, 2022)
Karst topography in Mfamosing limestone area has been observed to have little or no accurate information on the topography and relief of the area, which are the major determing factor for surface features such as Hills and valleys. Processes such as erosion, weathering, and denudation are seen to be relief control. Twenty one (21) locations in Ekintae East, proposed limestone quarry phase II sites, near Mfamosing village were accurately measured using Global Positioning System (Germin Oregon 550). The results indicates that elevations ranges from 12.0-76.0m and mean of 33.52m. Arch GIS suffer 10 softwares was used in contouring of the elevation map and 3-D surface elevation of the study area.The contour map of the area reveal South-West of the study area to be high relief with North-West, North-East and Southeast as low relief controlled by denudation. The limestone conduit systems are not necessarily constrained by surface topography, and hence the catchment for a particular karst unit may bear little or no relation to the surrounding topographic divides. Water from adjacent or adjoining non-karst landscapes can also contribute significantly to the catchments of karst units. This paper therefore is aimed at providing answers to the lowest and highest elevation points as well as the 3D surface elevation of Ekintae East, proposed Limestone quarry phase II as well as identifies diagnostic surface karst features and distinct differences in lithologies or disrupted surface drainage patterns in the area.